A SURVEY ON SPIROMETER BASED LUNG DISEASE DETECTION - Bhuvaneswari, N.; Ganapathy, Kirupa (International Journal of Psychosocial Rehabilitation, 2020)
Chronic Obstructive Pulmonary Diseases (COPD) is considered as one of the major causes of ill-health throughout the world. The effective way to diagnose various respiratory diseases is using spirometer. Spirometer is a device measures the amount of air volume and speed of the air that is inhaled and exhaled. With the help of spirometer, Chronic Obstructive Pulmonary Diseases (COPD) can be detected in advance and assess their condition without visits to medical centres. Spirometer comprises of 4 main segments-Spirometer body, hardware, Computer and Software. The spirometer body has differential pressure transducer which senses difference in air flow pressure, microcontroller is used to transmitting the data from circuit to the software to perform some computations and plot the graph.